2021
DOI: 10.3390/ijerph18041927
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Impact of Human–Cobot Collaborative Manufacturing Implementation on the Occupational Health and Safety and the Quality Requirements

Abstract: Implementing Industry 4.0 and interconnected robotization in industrial enterprises drifts towards occupational changes. Nowadays, the task is to create cooperation and collaboration between a robot and a human in a common robotized workplace so that it is safe and effective. The type of robot, the robotic device that works in collaboration with a human operator, is called a cobot. In the case of a closer interaction of the robot or cobot with humans, it is necessary to consider where it is possible to replace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 45 publications
(49 reference statements)
0
20
0
Order By: Relevance
“…only by the human participant and not by "the machine". Our work shows that it is possible to have an intelligent machine that regulates its actions to help the human, whatever strategy he adopts, which is an advantage for industry work (Pauliková et al, 2021). Furthermore, the current work showed that this new type of collaboration could be beneficial in terms of performance and usability.…”
Section: Discussionmentioning
confidence: 68%
“…only by the human participant and not by "the machine". Our work shows that it is possible to have an intelligent machine that regulates its actions to help the human, whatever strategy he adopts, which is an advantage for industry work (Pauliková et al, 2021). Furthermore, the current work showed that this new type of collaboration could be beneficial in terms of performance and usability.…”
Section: Discussionmentioning
confidence: 68%
“…According to the presented theoretical concepts, we may conclude that full implementation of stream and vector analysis in the practice of operational management of a bakery will result in us being able to speak of new quality in a fully digitised Bakery 4.0 (Pauliková et al 2021 ). This approach will allow for better management of the said bakery and will create competitive advantage in the market.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research argues that robots could replace workers in dangerous work environments, for instance, in chemical and mining industries, with a strong impact on the reduction of occupational injuries [ 16 , 17 ]. However, according to Yang et al [ 18 ], robot applications do not have a persistent impact on occupational injuries and can even increase the rate of occupational injuries in developing countries.…”
Section: Overviewmentioning
confidence: 99%
“…Workplace robotization is particularly suitable for work environments that involve hazardous chemical substances that are carcinogenic and toxic to humans. Robotization also helps to improve workplace ergonomics and to avoid, for humans, very laborious and often repetitive work [ 17 ]. The automation of tasks with robots can remove workers from hazardous situations, and cobots can facilitate access to work for aging workers or those with disabilities [ 12 ].…”
Section: Overviewmentioning
confidence: 99%